Oil palm in Colombia [2022] - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma (Federación Nacional de Cultivadores de de Palma de Aceite., 2022)
Oil palm is the most productive oilseed on the planet, a hectare planted produces 6 to 10 times more oil than any other oil seed. Colombia is the fourth larger producer of palm oil in the world and the first in America.
Keywords: Palma de aceite; Agroindustria de la palma de aceite; Estadística; Usos; Colombia; Salud y nutrición